Wastewater Purification: Aerobic Granulation in Sequencing Batch Reactors - Liu, Yu (CRC Press, 2009)
A newcomer to the scene, aerobic granulation is on its way to becoming the hot new technology for high-efficiency wastewater treatment. Thus far, intensive research has been conducted with regard to the understanding of the mechanism of aerobic granulation in sequencing batch reactors (SBR) and its application in treating a wide variety of municipal and industrial wastewater. This basic research has promoted the technology from laboratory-study all the way to the present pilot- and full-scale application. The time is right for a reference that discusses the technology and its application in wastewater purification.